GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE FOR SEED QUALITY PARAMETERS IN SOME OF THE LAND RACES OF SORGHUM - V. V. KALPANDE; P. A. KHADE; R. B. GHORADE; A. M. DANGE; S. B. THAWARI (The Bioscan, 2015)
Highest GCV was observed for threshed grain mold rating (38.97%) while lowest for the specific gravity of seed (1.66%). While for PCV, the highest value was recorded by one thousand seed weight (44.99%) while specific gravity of seed (2.00%) recorded the lowest value. The highest heritability estimate in broad sense was observed for threshed grain mold rating (99.08%) while the character 1000 seed weight (16.56%) recoded low heritability estimates. The highest values of expected genetic advance over mean was recorded for the characters threshed grain mold rating (79.90%) and lowest for specific gravity of seed (2.85%).The threshed grain mold rating and seed hardness exhibited high heritability along with high value of expected genetic advance per cent over mean which indicated the importance of these traits for selection. High value of heritability along with low value of expected genetic advance was observed for the characters like electrical germination percentage of seed, vigour index of seed and specific gravity of seed and heterosis breeding can be fruitfully exploited improving these characters.